Gu-Ben-Fang-Xiao Decoction Ameliorated Murine Asthma in Remission Stage by Modulating Microbiota-Acetate-Tregs Axis - Yingmei Dong; Yingmei Dong; Hua Yan; Hua Yan; Xia Zhao; Xia Zhao; Rui Lin; Lili Lin; Lili Lin; Yuanyuan Ding; Yuanyuan Ding; Liwei Liu; et al. (Frontiers Media S.A., 2020)
Dysbiosis of gut microbiota is a critical factor in the pathogenesis of asthma. Manipulating gut microbiota is a promising therapeutic intervention in asthma, and is being extensively studied. Gu-Ben-Fang-Xiao Decoction (GBFXD), derived from traditional Chinese medicine, is an effective and safe therapeutic formula for asthma in remission stage (ARS). Herein, we showed that GBFXD treatment remarkably alleviated ARS by improving respiratory function and lung histopathology. Asthmatic mice displayed a dysbiosis of gut microbiota, represented by significantly increased abundance of Bacteroidetes and decreased abundance of Firmicutes in gut, while GBFXD treatment reversed the gut dysbiosis in asthmatic mice at phylum, family, and genus levels. Moreover, our data showed that GBFXD treatment increased the abundance of short-chain fatty acid (SCFA)-producing bacteria in asthmatic mice, such as Firmicutes, Lachnospiraceae, and Bifidobacteriaceae, which consequently led to elevated levels of SCFAs. Furthermore, GBFXD treatment significantly enhanced the regulatory T cell differentiation via SCFAs, particularly acetate, in asthmatic mice. More critically, the protective effect of GBFXD was shown to be transmissible among asthmatic mice through co-housing microbiota transplantation. Antibiotic cocktail and acetate replenishment experiments also further substantiated the importance of SCFA-producing gut microbiota in GBFXD action. We, thus, demonstrated for the first time that gut microbiota dysbiosis existed in ARS. GBFXD could ameliorate ARS through the microbiota-acetate-Tregs axis.